PENGARUH KUALITAS LIMBAH BAGASSE SEBAGAI BAHAN BAKAR BIOMASSA TERHADAP EFISIENSI BOILER TIPE WATER TUBE - Hadi Prayitno; Tazzidane Olsen Ba’albaqi; M Dyan Susila; Harmen (Analit : Analytical and Environmental Chemistry, 2024)
Bagasse waste, a by-product of the sugar production process, has received attention as a biomass fuel. This bagasse waste can be utilized directly as boiler fuel for industrial needs. The effect of bagasse waste quality on boiler efficiency needs to be investigated to determine its potential as an alternative fuel. Sugarcane bagasse waste used as a boiler is first analyzed for quality such as Calorific Value, and ultimate and proximate analysis. Furthermore, the effect of using bagasse on boiler efficiency was observed. These data are taken from the boiler daily log book and laboratory. Analysis of the data obtained shows the optimal calorific value of the fuel used reaches 2347.48 kcal/kg. then, the most optimal boiler efficiency reaches 70.34%. While the heat losses that have been calculated reach up to 28%. The results of this study contribute to a broader understanding of the interaction of biomass fuel quality and industrial boiler performance, thus providing valuable insights for sustainable sugarcane waste management in the context of renewable energy production and environmental sustainability